Laparoscopic fundoplication in infants with life-threatening gastroesophageal reflux disease and associated anomalies as a predictor for surgical intervention - Sridhar, Ranjith Kumar; Sundaram, Jegadeesh; Bharathi, Selvapriya; Agarwal, Prakash; Ramasundaram, Madhu (Indian Journal of Child Health, 2020)
Gastroesophageal reflux disease (GERD) is most commonly seen in infancy. The symptoms abate without treatment in 60% of infants by the age of 6 months while approximately 90% of infants have complete resolution of symptoms by the age of 8–10 months. Infants with severe or life-threatening complications of pathological GERD that is unresponsive to medical therapy can be considered for surgical therapy despite their comorbid illnesses and increased risk for morbidity and mortality. The main type of anti-reflux surgery is fundoplication particularly laparoscopic Nissen fundoplication. Here, we describe a case series of four infants with life-threatening aspiration pneumonia who underwent laparoscopic Nissen fundoplication with gastrostomy button insertion in a single center performed by a single surgeon for complications arising from severe GERD, not responding to medical therapy. Out of four infants, three had complete resolution of symptoms and are thriving well highlighting the vital role played by this novel surgery in treating such infants after failed medical management. However, one infant died of severe morbidity in the post-operative period.